Analisis Sitiran Terhadap Skripsi Mahasiswa Tahun 2019 Program Studi Kimia Universitas Negeri Padang - Novelly, Shabrina; Ardoni (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2023)
This study aims to describe: 1) Citation patterns 2) Characteristics 3) The pattern of authorship in the 2019 Chemistry Study Program student thesis, uses citation analysis and uses descriptive methods with a quantitative approach. The population in this study were all thesis students of the 2019 Chemistry Study Program with data collection techniques using documentation techniques with citation analysis methods, namely citations contained in the thesis bibliography. The results of this study are: 1) The citation pattern in the thesis of the Chemistry Study Program, Faculty of Natural Sciences and Mathematics in 2019 is 2775 citations with an average of 38 citations in each thesis. 2) The characteristics of the literature in the thesis writing of the Chemistry Study Program students in 2019 mostly used journals as the main source of information with the number of citations 1901 citations or 69%, journals as many as 1901 citations or 69%, books as many as 416 citations or 15%. The number of citations in foreign languages compared to Indonesian shows that students of the 2019 Chemistry Study Program already have the ability to understand and master foreign languages, especially English. 3) the authorship pattern in the 2019 Chemistry Study Program student thesis from the author who is most frequently cited is Davidovits, J with a total of 10 citations. Meanwhile, the level of author collaboration is very high, with 1949 citations (70%) being multiple authors (more than one person) and the remaining 826 citations (30%) being single authors.